Performance of soybean plants subject to water deficit in different development stages - Brito, Leonardo Pereira da Silva; Santana, Farley Silva; Carvalho, Gabriel dos Santos; Chaves, Daniela Vieira (Scientia Agraria Paranaensis, 2021)
Soybean plants are constantly exposed to abiotic stresses that compromise production, among these, in areas of Brazilian Cerrado, mainly in the northeast region, periods of drought can occur due to irregular and summer rainfall. Thus, the objective of this work was to determine the physiological response of Monsoy 9350 soybean at different stages of development, when subjected to water stress. The experiment was conducted in a greenhouse, in the experimental area of the campus of the Universidade Federal do Piauí (UFPI) in Bom Jesus-PI, assembled in a 3x3 factorial scheme, with water in the soil at three levels (50% VTP; 75% VTP and 100% VTP) and three phenological phases, budding to bloom (BF); bloom to complete grain filling (FE) and budding to complete grain filling (BE), the experiment consisted of 9 treatments, in a randomized block design, containing 4 replications. The evaluation of the experiment was standardized according to the phenological stages and not according to the time. The following variables were evaluated: plant height, internode length, internode thickness, number of branches, chlorophyll index, number of flowers, insertion of the first pod and number of pods. According to the evaluated results, the water stress in soybean for cultivating Monsoy 9350 mainly affects the period from budding to bloom, interfering negatively in height, chlorophyll and number of pods.